Study of serum vitamin B12 levels in pregnant mothers and their newborns and its relation to growth of the infants - Jali, Sujatha; Gajjar, Rinkal; Kamate, Mahesh (Indian Journal of Child Health, 2022)
Introduction: The effect of vitamin B12 deficiency in pregnancy on the growth of infants has not been properly studied. Objectives: To study the correlation of vitamin B12 levels in pregnant mothers with vitamin B12 levels in their newborn infants and to know it’s relation to the growth of infants. Materials and Methods: Hundred full-term pregnant women and their newborns were enrolled from January 2011 to January 2012. Vitamin B12 levels were assessed and the growth of infants monitored till 6 months of age. Results: A total of 60 pregnant women (60%) had vitamin B12 deficiency while 29 newborns (29%) had low vitamin B12 levels. Vitamin B12 levels in the newborns had a strong positive correlation with mothers’ vitamin B12 levels (r=0.56; p<0.05). Babies born to vitamin B12 deficient mothers were shorter, and their mean weight at 6-month of age was significantly less. Conclusion: Vitamin B12 deficiency is very common in Indian pregnant mothers; it leads to vitamin B12 deficiency and growth retardation in their babies.